2022
DOI: 10.3390/fishes7040168
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Technical Efficiency in Exotic Carp Polyculture in Northern India: Conventional DEA vs. Bootstrapping Methods

Abstract: The paper adopts the conventional data envelopment analysis (DEA) and bootstrap procedure to analyze the technical efficiency, while tobit regression is applied to identify the factors affecting efficiencies of exotic fish polyculture in Jammu and Kashmir (India). According to the statistical analysis of the variables utilized, there was a lot of variability in the inputs being used by the farmers, with the most variation being in the lime input. The DEA estimated technical efficiency for the sample farms in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The potential for increasing technical efficiency can be seen from the input savings that can be made by producers, in which sugarcane farmers in Malang Regency are advised to reduce inputs by 16.6% and 14.6%, on both assumptions for a double bootstrap approach. The more significant input savings in the DEA bootstrap approach were found in [17], [37] study. The findings of this study highlight the importance of using a double bootstrap approach in assessing technical efficiency, as this method uncovers greater potential for input savings and increased efficiency among sugarcane farmers in Malang District compared to conventional DEA methods.…”
Section: Technical Efficiency Estimationmentioning
confidence: 78%
“…The potential for increasing technical efficiency can be seen from the input savings that can be made by producers, in which sugarcane farmers in Malang Regency are advised to reduce inputs by 16.6% and 14.6%, on both assumptions for a double bootstrap approach. The more significant input savings in the DEA bootstrap approach were found in [17], [37] study. The findings of this study highlight the importance of using a double bootstrap approach in assessing technical efficiency, as this method uncovers greater potential for input savings and increased efficiency among sugarcane farmers in Malang District compared to conventional DEA methods.…”
Section: Technical Efficiency Estimationmentioning
confidence: 78%
“…In depth, the existing empirical studies also tend to focus on the nexus between aging and technical efficiency across the world. For the example, Zhang et al, (2022) statistically revealed that aging have favorable impacts on technical efficiency of farmers in Indian farmers. Furthermore, Saiyut et al (2019) also investigated the effect of age structure on technical efficiency in the context of agriculture in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly,Liu et al, (2019) also statistically proved that aging of teaproducing farmers would exert negative impacts on technical efficiency in tea production of Meitan, China. By contrast,Zhang et al, (2022) statistically revealed that aging have favorable impacts on technical efficiency of farmers in Indian farmers. Nevertheless,…”
mentioning
confidence: 96%